В поисках белого бизона: повести / Т. М. Рид - Рид Томас Майн; Рид Томас Майн (2008)
Экземпляры: ф.9 (2011) / Инвентарный номер: 53808 / Цена: / Сис.шифр: 84(4Вел)-4 / Авт.знак: Р 49 / ГРНТИ: 17.82.31 / ББК: 84(4Вел)-44